Ultrasound and UV technologies for wastewater treatment using boron-doped diamond anodes - Crispim, Alana Carolyne (2022)
In recent years, electrochemical technologies have found a niche in the degradation of recalcitrant pollutants. In this critical review, some of the most promising electrochemical tools for the removal of aqueous organic pollutants from wastewater are discussed in detail. In particular, we discuss the use of ultrasound and ultraviolet irradiation to enhance electro-oxidation using boron-doped diamond anodes. A brief description of the current state of the most relevant studies, all of which are still at a low technology readiness level, is presented, as applied to synthetic solutions and real effluents in experiments on laboratory and pilot scales.